2017
DOI: 10.1007/s00424-017-1981-3
|View full text |Cite
|
Sign up to set email alerts
|

CK2 is a key regulator of SLC4A2-mediated Cl−/HCO3 − exchange in human airway epithelia

Abstract: Transepithelial bicarbonate secretion by human airway submucosal glands and surface epithelial cells is crucial to maintain the pH-sensitive innate defence mechanisms of the lung. cAMP agonists stimulate HCO3 − secretion via coordinated increases in basolateral HCO3 − influx and accumulation, as well as CFTR-dependent HCO3 − efflux at the luminal membrane of airway epithelial cells. Here, we investigated the regulation of a basolateral located, DIDS-sensitive, Cl−/HCO3 − exchanger, anion exchanger 2 (AE2; SLC4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Numerous CK2 consensus motifs have been identified on SLC4A2 aminoacidic sequence; most importantly, the exposure of both Calu-3 cells (a human lung cancer cell line) and primary human nasal cells to the CK2 inhibitor CX-4945 led to the almost complete inhibition of channel activity. 230 In the same way, it was shown that also the activity of TMEM16A, a Ca 2+ -activated chloride channel, is positively regulated by CK2; in fact, the TMEM16A conductance in CFBE airway epithelial cells is strongly hampered by both the pharmacological inhibition (mediated by TBB and CX-4945) and the transient downregulation of the α′ subunit of the kinase. 231 These data further support the strong CK2 involvement in chloride and hydrogen carbonate homeostasis, that in the airway epithelia is fundamental for adequate solubilization and excretion of mucus, as well as for efficient antimicrobial action.…”
Section: Ck2 In Human Diseasesmentioning
confidence: 93%
“…Numerous CK2 consensus motifs have been identified on SLC4A2 aminoacidic sequence; most importantly, the exposure of both Calu-3 cells (a human lung cancer cell line) and primary human nasal cells to the CK2 inhibitor CX-4945 led to the almost complete inhibition of channel activity. 230 In the same way, it was shown that also the activity of TMEM16A, a Ca 2+ -activated chloride channel, is positively regulated by CK2; in fact, the TMEM16A conductance in CFBE airway epithelial cells is strongly hampered by both the pharmacological inhibition (mediated by TBB and CX-4945) and the transient downregulation of the α′ subunit of the kinase. 231 These data further support the strong CK2 involvement in chloride and hydrogen carbonate homeostasis, that in the airway epithelia is fundamental for adequate solubilization and excretion of mucus, as well as for efficient antimicrobial action.…”
Section: Ck2 In Human Diseasesmentioning
confidence: 93%
“…For instance, cAMP agonists activate the Cl − channel CLCN2 [ 34 ], SLC26A9 [ 35 ], the Cl − /HCO 3 − exchanger pendrin (SLC26A4) [ 36 ], the Na + /HCO 3 − cotransporter NBCE1 [ 37 ] and the H + /K + ATPase HKA2 (ATP12A) [ 29 , 38 ]. Additionally, it has been shown that cAMP modulates the expression of the Cl − /HCO 3 − exchanger type 2 (AE2 or SLC4A2) in airway epithelial cells [ 29 , 39 , 40 ]. Furthermore, cAMP mediates K + signaling, e.g., by activation of the basolateral membrane K + channel KCNQ1 [ 39 , 41 ], which is associated with chloride secretion [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, cAMP agonists activate the Cl - channel SLC26A9 [33], the Cl − /HCO3 − exchanger pendrin (SLC26A4) [34], the Na + /HCO3 - cotransporter NBCE1 [35], and the H + /K + ATPase HKA2 (ATP12A) [28,36]. Additionally, it has been shown that cAMP modulates the expression of the Cl - /HCO3 - exchanger type 2 (AE2 or SLC4A2) in airway epithelial cells [28,37,38]. Furthermore, cAMP mediates K + signaling, e.g.…”
Section: Discussionmentioning
confidence: 99%